Issues And Challenges Of Black Magic Criminal Convictions In Syariah Courts: A Review - Lukman Abdul Mutalib; Mohd Faisal Mohamed; Kamarul Arifin Mohd Wafa; Fathiyyah Mohd Fakhruddin; Wan Abdul Fattah Wan Ismail; Ahmad Syukran Baharuddin; Abd Hamid Abd Murad (Science and Engineering Research Support Society, 2024)
Indexed by ERA